Dysfunction of Optineurin in Amyotrophic Lateral Sclerosis and Glaucoma - Toth, Reka P.; Atkin, Julie D. (Frontiers in Immunology, 2018)
Neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS), frontotemporal dementia, and glaucoma, affect millions of people worldwide. ALS is caused by the loss of motor neurons in the spinal cord, brainstem, and brain, and genetic mutations are responsible for 10% of all ALS cases. Glaucoma is characterized by the loss of retinal ganglion cells and is the most common cause of irreversible blindness. Interestingly, mutations in OPTN, encoding optineurin, are associated with both ALS and glaucoma. Optineurin is a highly abundant protein involved in a wide range of cellular processes, including the inflammatory response, autophagy, Golgi maintenance, and vesicular transport. In this review, we summarize the role of optineurin in cellular mechanisms implicated in neurodegenerative disorders, including neuroinflammation, autophagy, and vesicular trafficking, focusing in particular on the consequences of expression of mutations associated with ALS and glaucoma. This review, therefore showcases the impact of optineurin dysfunction in ALS and glaucoma.